Unusual medial tibial plateau fracture fixation using dual plating - Bora S., Shradha; L., Senthil; U., Thiyagarajan; J. P., Pradeep; Raj D., Gokul (International Journal of Research in Orthopaedics, 2019)
Background: Medial tibial plateau fractures is a subtype of proximal tibial fractures that involve the articular surface and can present in several distinct patterns. Purpose of this study was to assess the clinical outcome of stabilizing these biplanar medial tibial plateau fractures using dual plating technique through a single incision. Methods: Between 2017 to 2019, 12 men and 8 women with closed medial tibial plateau fracture who underwent reconstruction using two plates through a posteromedial approach were included in the study group. The fractures were classified using the three column concept of Lou. Results: One patient had an articular step off that was unacceptable and two patients had an acceptable articular step off. Functional assessment was done using the objective scoring of Oxford knee score criteria and radiological assessment was done using the Rasmussen modified score. Conclusions: Biplanar reconstruction using dual plates is a reliable and safe technique to reconstruct complex medial tibial plateau fractures.